Thrombotic storm, hemostasis disorders and thromboinflammation in COVID-19 - A. D. Makatsariya; E. V. Slukhanchuk; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; A. S. Shkoda; S. V. Akinshina; N. A. Makatsariya; V. I. Tsibizova; J.-C. Gris; I. Elalamy; С. Ay; et al. (IRBIS LLC, 2021)
The rate of thrombosis and disseminated intravascular coagulation (DIC) has been increasing in COVID-19 patients. Key features related to such condition include minimal or no risk of bleeding, moderate thrombocytopenia, high plasma fibrinogen as well as complement components level in the areas of thrombotic microangiopathy. The clinical picture is not typical for classic DIC. This review systematizes the pathogenetic mechanisms of hypercoagulation in sepsis and its extreme forms in patients with COVID-19. The latter consist of the thrombosis-related immune mechanisms, the complement activation, the macrophage activation syndrome, the formation of antiphospholipid antibodies, the hyperferritinemia, and the dysregulation of the renin-angiotensin system. Taking into consideration the pathogenetic mechanisms, the biomarkers had been identified related to the prognosis of the disease development. Patients with pre-existing cardiovascular disease and other risk factors, including obesity, diabetes, hypertension, and aging pose the peak risk of dying from COVID-19. We also summarize new data on platelet and endothelial dysfunction, immunothrombosis, and, as a result, thrombotic storm as essential components of COVID-19 severe features.